(untitled) (Research, Society and Development, 2025)
The overall objective of this study is to analyze, through a literature review, the importance of strength training as an effective tool for mitigating the negative effects of aging, promoting health, autonomy, and quality of life in the elderly population. Regular physical activity is essential at all stages of life and takes on an even more important role in aging, promoting physical, psychological, social, and physiological benefits. Among the elderly, strength exercises stand out for maintaining or increasing muscle mass, preventing weakness and functional limitations that increase the risk of falls. Furthermore, balance exercises contribute to reducing fractures and increasing autonomy. Research indicates that, although muscular adaptations occur to a lesser extent in older individuals, they are similar to those in younger individuals when training is well-structured, with training volume being a decisive factor for hypertrophy. On the other hand, studies show that strength gains in older individuals are also strongly related to neural adaptations, especially in the early stages of training. In Brazil, where the population aged 65 and over grew by more than 57% between 2010 and 2022, a sedentary lifestyle represents a growing challenge. In this scenario, physical education professionals play a key role in developing strategies to combat inactivity and promote quality of life and healthy longevity.